A cooperação no Atlântico Sul e uma análise da proteção da Zona de Paz e Cooperação do Atlântico Sul: estudo de caso das Marinhas do Brasil e de Camarões - Terror, Isabela Sequetto (2018)
The present work, “Cooperation in the South Atlantic and an analysis of the projection of the South Atlantic Peace and Cooperation Zone. Case study of the Brazilian and Cameroon Marines”, tries to approach a case study between the Navy of Brazil and Cameroon. The relevance of the study rests on the need to better understand Brazil's attempt to exert a strong influence in the South Atlantic, through cooperation with the African countries, to project itself on the international scene. Thus, the objective is to present the theoretical bases that support the cooperation practiced by Brazil as well as the use of the Inter-Dependency Theory to interconnect the States, in addition, it proposes to detect Brazil's role in ZOPACAS, to identify the importance given by Brazil with regard to cooperation with Cameroon, and to identify the actions carried out by Brazil in the scope of cooperation with the African country, taking into account the National Defense Policy and the National Defense Strategy. For that, the exploratory method will be used, with documentary and bibliographical revision referring to the theme. Thus, it is observed that even during the period that Brazil did not devote its attention to the presence in matters related to the South Atlantic, the country retained interest in maintaining close relation with Africa, seeking to have greater projection in the inter-national scenario. In order to do so, it acts and mobilizes the revitalization of ZOPACAS, enabling trust among member states when implementing cooperation that will benefit both sides of the relationship. Thus, due to Brazil's attempt to play an important and prominent international role in this matter, this country seeks to increase its influence with the countries of the South Atlantic. It is concluded that, with this study and the annex documents, the navies of Brazil and Cameroon are approaching and establishing partnerships, allowing greater integration between these countries and the South Atlantic, projecting Brazil in the international scenario.